Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1017/s0022172400027108
|View full text |Cite
|
Sign up to set email alerts
|

Weather, host and vector – their interplay in the spread of insect-borne animal virus diseases

Abstract: The spread of insect-borne animal virus diseases is influenced by a number of factors. Hosts migrate, move or are conveyed over long distances: vectors are carried on the wind for varying distances in search of hosts and breeding sites; weather and climate affect hosts and vectors through temperature, moisture and wind. As parasites of host and vector, viruses are carried by animals, birds and insects, and their spread can be correlated with the migration of hosts and the carriage of vectors on winds associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 67 publications
4
107
0
Order By: Relevance
“…Some vectors, such as mosquitoes and midges, are capable but not very strong fliers, with forward speeds in still air of approximately 0.5 m/s (12). In tranquil air, the direction and distance of movement are limited by the vector' s ability to find its bearings, and by air speed and flight duration.…”
Section: Vector Range Of Culicoidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some vectors, such as mosquitoes and midges, are capable but not very strong fliers, with forward speeds in still air of approximately 0.5 m/s (12). In tranquil air, the direction and distance of movement are limited by the vector' s ability to find its bearings, and by air speed and flight duration.…”
Section: Vector Range Of Culicoidesmentioning
confidence: 99%
“…In the absence of wind or at wind speeds of less than 2 m/s, insects can fly unaided when seeking shelter, hosts, mates and oviposition sites (12). Insect movement can be divided into station-keeping movements, in which the insect remains within its current habitat, and movements that take it away, permanently or for long periods, from the home patch (14).…”
Section: Short-range Dispersal Of Culicoides Midgesmentioning
confidence: 99%
“…For several diseases, it has been suggested that wind-blown insect vectors could have been responsible for the spread of the virus to previously unaffected areas (61), such as the entry of BT into Europe (62) and Australia (63) and of JE into Australia (64). Wind-spread models have been developed to model such dispersions and may be used to identify areas at risk of arboviral incursion due to windborne insects (65,66,67).…”
Section: Participatory Surveillancementioning
confidence: 99%
“…24,25 Climatic factors (rainfall, temperature, and humidity) influence mosquito survival, and temperature affects the speed at which the virus can replicate. 26,27 The geographic range of dengue transmission has been shown to closely mirror average humidity (which is strongly linked to rainfall and temperature). 28 Based on this established dengue-humidity relationship, we estimated a southward expansion of the dengue zone -that is, the region with climatic conditions suitable for supporting the mosquito vector.…”
Section: Denguementioning
confidence: 99%